Hygroscopic analysis of individual Beijing haze aerosol particles by environmental scanning electron microscopy. (January 2018) - Bai, Zhangpeng; Ji, Yuan; Pi, Yiqun; Yang, Kaixiang; Wang, Li; Zhang, Yinqi; Zhai, Yadi; Yan, Zhengguang; Han, Xiaodong
Abstract: Investigating the hygroscopic behavior of haze aerosol particles is essential for understanding their physicochemical properties and their impacts on regional weather and visibility. An environmental scanning electron microscope equipped with a home-made transmission-scattering electron imaging setup and an energy dispersive spectrometer was used for in-situ observations of pure water-soluble (WS) salts and Beijing haze particles. This imaging setup showed obvious advantages for improving the resolution and acquiring internal information of mixed particles in hydrated environments. We measured the deliquescence relative humidity of pure NaCl, NH4 NO3, and (NH4 )2 SO4 by deliquescence–crystallization processes with an accuracy of up to 0.3% RH. The mixed haze particles showed hygroscopic activation like water uptake and morphological changes when they included WS components such as nitrates, sulfates, halides, ammoniums, and alkali metal salts. In addition, the hygroscopic behavior provides complementary information for analyzing possible phases in mixed haze particles. Highlights: In-situ hydrated observations on mixed haze particles were performed by ESEM. Transmission scattering electron imaging improved resolution in wet environment. Composition/morphology related hydrated behavior of haze particles was obtained. Mixed haze particles containing WS components displayed hygroscopic activation.